Adopting vulnerability and power-sensitive pluralism for a pragmatist turn in policy-advice. Impulses from a critical framework of public health - Ana Honnacker; Julian Prugger; Tizia Rosendorfer; Anne Meuche; Michael Reder; Christian Apfelbacher (Critical Public Health)
Following the assumption that pragmatism offers an alternative, non-reductionist understanding of evidence or science-based policy-making, we critically examine and reconstruct the preconditions of such a pragmatist turn. We argue that pragmatist theory, in general, lacks an explicit normative foundation for critical value judgements and that it tends to overlook power dynamics and asymmetries in social relations. First, we propose the adoption of vulnerability as a normative guideline. From this perspective, the conflicting differences and power struggles that occur in pluralist societies are highlighted. Second, we argue that accounts of pluralism must involve practices of conflict and politically articulated exclusion. Therefore, we suggest an alternative understanding of pluralism that acknowledges and addresses the underlying social and historical conditions, thereby evading the risk of reproducing established modes of exclusion and the production of vulnerabilities.